Discurso publicitário como dispositivo disciplinar: os impactos da campanha "Real Universitário" na recepção do público jovem - Vaz, Natália de Alcântara (2008)
This M.A. paper has as the main object the publicity campaign "Real Universitário", made in 2006 by Banco Real, and its impacts on the discourse of the receptors about their consumption practices of banking services and administration of their finances. The main objective is to analyze the publicity as a disciplinary tool, a discourse that supports and propagates ways of normalization of consumption and the financial behavior of young undergraduates who are the target of the campaign. The secondary objectives are how to identify the disciplinary aspects of banking publicity and analyze how the reception interacts with such aspects. We believe that, by being inserted in the universe of human sciences - more specifically, of communication - the publicity, as well as other modern knowledge, is a mechanism the society disposes itself to discipline and normalize. We have, as a methodology, firstly made a bibliographic research that permeates all the methodological stages of this study. The philosopher Michel Foucault is the main theoretic ground developed here. We have also made an exploratory documental research to the selection of corpus. For the analysis of this material, we combines the reflections arisen from transition of the first and second period of Foucault studies - the archeology and the genealogy respectively which served as support to the considerations over the publicity as a discourse of discipline -, with the precepts of Discourse Analysis of French line. For the empirical research we employed the focus group technique, as the nature of the necessary datas is qualitative and for the analysis of the results, the discipline was our guide.